Reflexive adaptation for resilient water services: Lessons for theory and practice. (July 2019) - Westling, E.L; Sharp, L.; Scott, D.; Tait, S.; Rychlewski, M.; Ashley, R.M.
Highlights: Three forms of adaptation are identified; scientific, collaborative, reflexive . Practical examples of reflexive adaptation are missing. An 'Adaptive Planning Process' (APP) applying reflexive adaptation is introduced. The APP's three linked workshops were co-developed and trialled in a water utility. Reflexive adaptation enables new ways of addressing uncertainties and resilience. Abstract: 'Adaptive management' concern attempts to manage complex social-ecological and socio-technical systems in nimble ways to enhance their resilience. In this paper, three forms of adaptive management are identified, 'scientific' forms focused on collation of scientific data in response to management experiments, but more recent developments adding processes of collaboration as well as emphasising the need for reflexivity, that is, conscious processes of opening up debates to different perspectives and values. While reflexive adaptive management has been increasingly discussed in theory, there is a lack of examples of what its application means in practice. As a response, this paper examines an 'Adaptive Planning Process' (APP), seeking to apply reflexive adaptive management as a means to improve climate resilience in the UK water sector. The APP's three inter linked workshops – Aspiration, Scenario and Roadmapping – were co-developed and trialled in a water utility. By describing and justifying the choices made in the development of the APP, the paper aims to reveal some of the challenges that arise when trying to design processes that achieve reflexive adaptation. The paper concludes that, if applied to planning for climate change, reflexive adaptation has the potential to explore multiple value positions, highlight different potential futures and acknowledge (and hence, partly address) power differentials, and therefore to offer the possibility of real change. On the basis of the trial, we argue that through tapping the depth and breadth of internal knowledge the APP process created the potential for decision making to be joined up across different parts of the utility, and hence offering new strategies and routes for addressing uncertainties and delivering more resilient water services.